INTERELASI KOMPENSASI DAN BEBAN KERJA TERHADAP TURNOVER INTENTION PADA SEKTOR INDUSTRI TEKSTIL DI BANDUNG - Devy Devy; Grace Orlyn Sitompul (POLITEKNIK LP3I JAKARTA, 2024)
Examine the impact of compensation and work pressure on the desire of workers to quit the textile industry sector companies in Bandung. The research is a quantitative research involving 100 employees working in the textile industry in Bandung. The Data were taken using questionnaires and data processed using statistical methods to predict the linear dependent variable with SPSS version 25. The achievement of the following research analysis is the result of commensurate findings and some that are not and simultaneously the impact of compensation and workload on the employee's desire to resign. The achievement of the explanation analysis showed that the compensation effect did not show a big impact on the employee's intention to leave the company on the other hand the complexity of the work has a high value as a driving factor that causes employees to leave their jobs. Key words: Compensation, Workload, Turnover Intention